The effects of unilateral cortical and tectal lesions on retinal ganglion cells in rats. - Perry, V; Cowey, A (1979)
The ganglion cell layer of the retina was examined for retrograde transneuronal degeneration after removing the striate cortex unilaterally in infant or adult rats. No significant degeneration occurred, even after a survival time of 15 months, and the rat is therefore unlike other mammals in which the phenomenon has been studied. A possible explanation that most optic axons bifurcate in rats and that the tectal branch can sustain the ganglion cell after the branch to the dorsal lateral geniculate nucleus has degenerated following removal of striate cortex was ruled out by the demonstration that combined unilateral removal of striate cortex and superior colliculus in adults was similarly ineffective. Unilateral removal of the superior colliculus alone also failed to affect ganglion cells of adult rats but produced conspicuous degeneration in infants. The greater vulnerability of the infantile developing visual system casts doubt on the common assumption that the effects of brain damage are less severe in infants than adults.